(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Vipādika is a common disorder of skin which affects the people irrespective of age and sex. Due to its severity and chronicity it hampers the daily activities of an individual. The main symptom for Vipādika is Daranam (crack) which presents along with Kandu (itching), Vedana (pain). Objective: A clinical study was conducted to evaluate the effect of Chitrakadi lepa with Punarnavadi kashaya in Vipadika. Materials and method: The study design is interventional study-pre and post-test with a sample size of 15 patients with signs and symptoms of Vipādika belonging to age group 20-60 years, attending the OPD of Agadatantra department, Govt. Ayurveda College, Thiruvananthapuram were selected. Patients on corticosteroids, pregnant and lactating woman are excluded. Before intervention, 25gm of Avipathy choornam was given for Anulomana. The study group was given Punaṙnavādi kaṣaya (48ml) internally twice daily half an hour before food and Chitṙakādi lepa mixed with Gritha and Tila taila was applied externally twice daily for 30 days. After completion of treatment, a follow up period of 15 days was advised. Symptomatic assessment was done before the treatment, 15th day, after the treatment (31st day) and after follow up period 45th day. The outcome variables like no. of crack, pain, itching, and nature of crack were assessed. Results and Discussion: Result was analysed statistically using non parametric statistical test - Freidmans test with Dunnets multiple comparison test (post-hoc). The result obtained was highly significant in relieving the cardinal symptoms of Vipādika especially pain.